THE SUSTAINABLE DEVELOPMENT OF AN INDUSTRIAL CLUSTER IN THE CONTEXT OF CORPORATE SOCIAL RESPONSIBILITY – A NEW CHALLENGE FOR CLUSTER MANAGEMENT - Bembenek, Boguslaw (European Scientific Journal, ESJ, 2015)
In the present article, clusters are treated as a form of contemporary organisation, which is created as a result of reciprocal interactions, formal and informal, horizontal and vertical relations between geographically concentrated heterogeneous subjects specialised in a particular area, which represent the environment of: business, science, business support and local public administration. The author assumed that the condition for the achievement of the determined strategic goals of sustainable development within an industrial cluster is, inter alia, its endogenic ability to create eco-innovations. Moreover, he indicated that the realisation of the assumptions of the concept of sustainable development is an integral element of CSR philosophy. Taking into consideration the significance as well as the internal and external dimensions of CSR, the author enumerated multitudinous benefits that ensue from socially responsible cluster management. He emphasised that socially responsible activity of an industrial cluster, which is consistent with the assumptions of sustainable development, can contribute to the permanent improvement of a society’s quality of life, without considerable negative changes in natural environment and loss of socio-cultural values. Hence, it is necessary to prepare and include proper rules of sustainable, socially responsible development in the contents of strategic documents, including the declaration of missions and visions and their constant observance in every area of activity, in internal and external environment.